5(-2x+5)+x-5=-43

Simple and best practice solution for 5(-2x+5)+x-5=-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-2x+5)+x-5=-43 equation:



5(-2x+5)+x-5=-43
We move all terms to the left:
5(-2x+5)+x-5-(-43)=0
We add all the numbers together, and all the variables
x+5(-2x+5)+38=0
We multiply parentheses
x-10x+25+38=0
We add all the numbers together, and all the variables
-9x+63=0
We move all terms containing x to the left, all other terms to the right
-9x=-63
x=-63/-9
x=+7

See similar equations:

| X²+9x-1620=0 | | t-9-3.2=2 | | 43=y+18 | | 2m2+5m+16=8 | | 2z-z-1=11 | | .25x-5=20 | | 4x/3+7/3=0 | | 4c+6c=10 | | (2x-1)^2=81 | | 1/2(c+3)=2/5c-3/4 | | t+9-9.2=9 | | -20=-4x–6x | | 14=1/3y | | 16x+9=16x-48 | | k+4—5(k+2)=3k—2. | | y²-6=2²+3²-6-(-3) | | -(-13+b)=27 | | 5x+7-3x=1/2(4x+12)+1 | | -44=-14x+28+6x | | 5x+4+3x+10=180 | | F(0)=2x^2+x-1 | | |8-3x|=0 | | 2x+8=5×-3 | | 7w-13=5w-7 | | -6x-18=-72 | | 3/2-w=5/2 | | -7(x+1)=-41x+55 | | -4m+1=-19 | | 5x-16·3x-12=0 | | –3x+0.8=–1.4 | | 40=1+3x | | 200m-100m+52250=56375-175m |

Equations solver categories